Konstruksi Sosok Ibu Disabilitas Netra dalam Iklan Dancow Fortigro di Youtube - Putri, Fathia Aqila Zahra; Delliana, Santi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
The mother figure is a very important figure and also has a big role in the family. In the Dancow Fortigro advertisement entitled “My mother is different, but #LoveBundaSempurna” the figure of a mother with a visual disability appears predominately. This study aims to determine the construction of the figure of a mother with visual disabilities who appears in Dancow Fortigro's advertisement entitled "My Mother is Different, but #CintaBundaSempurna" by using the constructivism paradigm. This study was examined using Charles Sanders Peirce's semiotic analysis, which has three elements of meaning, namely sign, object, and interpretant. The results of this study found that the figure of a mother with disabilities in the Dancow Fortigro ad has maternal instincts, continues to play a domestic role, has independence, educates children to be independent, and still needs help from others.